Underwater temperature and pressure monitoring for deep-sea SCUBA divers using optical techniques - Mirza, Jawad; Kanwal, Firdos; Salaria, Umair Ahmad; Ghafoor, Salman; Aziz, Imran; Atieh, Ahmad; Almogren, Ahmad; Haq, Anwar Ul; Kanwal, Benish (Frontiers in Physics, 2024)
The safety of SCUBA divers remains at high risk in deep-sea owing to multiple factors such as dangerous surrounding, rely upon technical equipment necessary for life support, decreased underwater navigation, and communication infrastructure. Gradual decrease and increase in water temperature and pressure, respectively corresponding to depth are among the most common problems that cause most of the fatalities in deep-sea diving. Therefore, different gadgets for accurate measurement of vital parameters, reliable navigation, and seamless communication are of prime importance. In this paper, we propose an all-optical technique for local and remote monitoring of underwater temperature and pressure for deep-sea SCUBA divers based on fiber Bragg grating (FBG) sensors and underwater optical communication-single mode fiber (UWOC-SMF) integrated transmission system. The proposed technique is implemented using two FBG temperature and pressure sensors fixed over diver's suit and UWOC-SMF integrated transmission system for simultaneous local and remote monitoring of underwater temperature and pressure.Remote monitoring of underwater temperature and pressure is achieved at ship station through a remotely operated underwater vehicle (ROV) and UWOC-SMF integrated transmission system by means of shifts in the original Bragg wavelengths of sensors due to temperature and pressure variations. The performance of the sensors is analyzed for temperature and pressure in the range of 0 to 6.4 MPa (≈0 to 655 mH 2 O) and 40 to -2 o C, respectively corresponding to different depths.The results show that the proposed technique can work well in the deep ocean over a range